Promosi, Kualitas Produk Dan Harga Terhadap Pengaruh Pengambilan Keputusan Pembelian Pada PT Ananda Jataka Bayu Sejahtera Surabaya - Dewi Anggraini; Ahmad Daengs GS; Harsono Teguh Santoso (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
Competition in the world of extreme effort to win the competition, companies must be able to provide satisfaction to its customers, by providing better than its competitors. This study aims to determine the effect of promotion, product quality and price of goods affect the purchase decisions on the PT. Ananda J Bayu Sejahtera Surabaya.The data used in this study are primary data, ie data obtained by distributing questionnaires to the respondents, the buyer PT. Ananda J Bayu Sejahtera Surabaya as research object. The analysis technique used in this study is used F test and t test.The result of the calculation processing of data obtained calculated F value of 67.430 bigger than F tables 2.734 which means the sale (X1), product quality (X2) and price (X3) significantly influence the purchase decision. The test results obtained partial t-count equal to 8.093 is greater than t-table is 1.996, meaning the partial sale can influence the purchase decision peutusan significantly. The test results obtained partial 3,780 t count bigger than t-table is 1.996, meaning that the quality of the product is able to significantly influence the purchase decision. The test results obtained partial t-count of 2,588 is greater t-table of 1.996, meaning the price is able to significantly influence the purchase decision.